PENGARUH LITERASI POLITIK TERHADAP PARTISIPASI POLITIK PEMILIH PEMULA PADA PEMILUKADA KOTA PARIAMAN TAHUN 2018 - Huzaifa Katarudin; Nora Eka Putri (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2020)
The aim of this study is to analyze the effect of political literacy on political participation of Novice voters in the 2018 regional elections for Pariaman city. The not optimal participation of Novice voters in regional elections and the relatively high level of apathy for first-time voters and minimal knowledge of politics makes first-time voters vulnerable to mobilization, this is a reason for researchers to make novice voters the object of research. The method used in this research uses a quantitative approach with a survey method. The population in this study were adolescents or people aged 17-23 years who were registered as voters by the KPU of Pariaman City. Determination of sample using Simple Random Sampling technique resulted in 100 samples. Data collection uses a liker scale. The data obtained were analyzed using simple regression. The results showed that the political literacy variable simultaneously had a significant effect on the political participation of first-time voters in Kota Pariaman in 2018.